2017
DOI: 10.3344/kjp.2017.30.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Hindi version of short form of douleur neuropathique 4 (S-DN4) questionnaire for assessment of neuropathic pain component: a cross-cultural validation study

Abstract: BackgroundPain with neuropathic characteristics is generally more severe and associated with a lower quality of life compared to nociceptive pain (NcP). Short form of the Douleur Neuropathique en 4 Questions (S-DN4) is one of the most used and reliable screening questionnaires and is reported to have good diagnostic properties. This study was aimed to cross-culturally validate the Hindi version of the S-DN4 in patients with various chronic pain conditions.MethodsThe S-DN4 is already translated into the Hindi l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…The sensitivity and specificity of our version of the questionnaire were 75% and 95.3%, respectively, for test 1, and 76.2% and 98.8%, respectively, for test 2, which were the highest at the cut-off value 4 or more. This finding is in accordance with most of the validation studies (7,9,11). There are, however, validations done in Dutch (23) and New Arabic (22) languages, and both found the cutoff value at 5/10.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The sensitivity and specificity of our version of the questionnaire were 75% and 95.3%, respectively, for test 1, and 76.2% and 98.8%, respectively, for test 2, which were the highest at the cut-off value 4 or more. This finding is in accordance with most of the validation studies (7,9,11). There are, however, validations done in Dutch (23) and New Arabic (22) languages, and both found the cutoff value at 5/10.…”
Section: Discussionsupporting
confidence: 92%
“…Based on our study, the most frequent complaints that patients with neuropathic pain had were burning pain, electrical sensation, tingling sensation, and numbness. When this is compared with other studies, we found variations (7,22,23). We believe that neuropathic pain consists of a collection of symptoms and signs that may also depend on the type of disease, so rather than focusing on any specific item for predicting neuropathic pain, one must consider the cutoff value.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15][16] e original French version of DN4 questionnaire has very good sensitivity (83%) and specificity (90%) for the identification of chronic NP as a consequence of a lesion or disease of the nervous system (either peripheral or central). [3] Various researchers, including Bouhassira et al [3] and Gudala et al, [17] have validated an interview version of the DN4 or Short form of DN4 including only 7 self-completing items on various NeP symptoms and not the whole 10 items. e reason for pursuing the short form and not the complete DN4 was the ease and lack of manpower and time by both the studies.…”
Section: Introductionmentioning
confidence: 99%